EVALUASI TINGKAT KEPATUHAN WAJIB PAJAK UMKM DI KPP PRATAMA KOTA SAMPIT - Alia Afifah; Rusniati; Rifani, Ahmad (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
This study aims to evaluate the tax compliance level of MSME taxpayers registered at the Sampit Primary Tax Office (KPP Pratama) during the 2022–2024 period. The study employed a quantitative descriptive method using documentation and interviews to collect primary and secondary data. The findings show that the average compliance rate among MSME taxpayers remains low, at only 20.68%. The primary factors behind this low compliance include limited tax knowledge, lack of awareness, and suboptimal outreach efforts by tax authorities. The implementation of Government Regulation No. 23 of 2018, which lowered the final tax rate, had a positive impact but was not sufficient to significantly boost compliance.